La influencia de material didáctico en el proceso de enseñanza aprendizaje, en los estudiantes del 8vo, 9no y 10mo año de educación básica, en el área de estudios sociales de la Unidad Educativa Simón Bolívar del cantón Machala en el periodo lectivo 2013-2014. - Benitez Chica, José Miguel (2015)
This research is based on a process of bibliographic and field research, the study is called, The influence of teaching materials in the teaching-learning process, students in 8th, and 9th and 10th year of basic education, in the area of Social Studies Education Unit Machala Canton Simon Bolivar in the academic year, 2013-2014.